Long-term evaluation of temporomandibular disorders in association with cytokine and autoantibody status in young women. (August 2021) - Son, Chunghwan; Park, Yoon Kyung; Park, Ji Woon
Highlights: Levels of IL-8 and IgG were significantly higher in the high disability group. Certain cytokine and chemokine levels showed significant effects on jaw function and pain. More severe TMD pain is associated with higher levels of systemic inflammation. Abstract: Temporomandibular disorders (TMD) is a chronic pain disease affecting 4–60% of general population. Its suggested etiology includes mechanical overloading to related structures, psychosocial factors, and genetic vulnerability. However, its pathogenesis is yet to be fully understood, especially in cases with a higher level of pain and more associated comorbidities. Recently chronic systemic inflammation and possible autoimmunity has been indicated in several pain conditions as the underlying mechanism of chronicity but this aspect has not been rigorously investigated in TMD. This article focuses on analyzing the levels of cytokines, chemokines, autoantibodies and nonspecific inflammatory markers and comparing their levels according to pain severity and duration in 66 female TMD patients in their 20 s and investigating their association with clinical indices of TMD and comorbidities. The high pain disability group showed decreased range of jaw function and more pain on palpation of capsule areas compared to the low pain disability group. Comorbidities such as anxiety and sleep disturbance were also significantly more prevalent. The level of IL-8 and IgG were significantly higher in the high pain disability group. IL-2, -8, -13, IFN- γ, RANTES, PGE2, and thrombopoietin levels showed a significant effect on indices reflecting jaw function, generalized pain intensity, and health related quality of life. Such results imply that longer pain duration and higher pain intensity is associated with higher levels of systemic inflammation suggesting the possible role of immunologic disturbance as an underlying factor of chronic TMD pain and warranting further investigation for its consideration in diagnosis and treatment.